Impacts of gantry angle dependent scanning beam properties on proton PBS treatment. (20th December 2016) - Lin, Yuting; Clasie, Benjamin; Lu, Hsiao-Ming; Flanz, Jacob; Shen, Tim; Jee, Kyung-Wook
Abstract: While proton beam models in treatment planning systems are generally assumed invariant with respect to the beam deliveries at different gantry angles. Physical properties of scanning pencil beams can change. The gantry angle dependent properties include the delivered charge to the monitor unit chamber, the spot position and the spot shape. The aim of this study is to investigate the extent of the changes and their dosimetric impacts using historical pencil beam scanning (PBS) treatment data. Online beam delivery records at the time of the patient-specific qualify assurance were retrospectively collected for a total of 34 PBS fields from 28 patients treated at our institution. For each field, proton beam properties at two different gantry angles (the planned and zero gantry angles) were extracted by a newly-developed machine log analysis method and used to reconstruct the delivered dose distributions in the cubic water phantom geometry. The reconstructed doses at the two different angles and a planar dose measurement by a 2D ion-chamber array were compared and the dosimetric impacts of the gantry angle dependency were accessed by a 3D γ -index analysis. In addition, the pencil beam spot size was independently characterized as a function of the gantry angle and the beam energy. The dosimetric effects of the perturbed beam shape were also investigated. Comparisons of spot-by-spot beam positions between both gantry angles show a mean deviation of 0.4 and 0.7 mm and a standard deviation of 0.3 and 0.6 mm for x and y directions, respectively. The delivered giga-protons per spot show a percent mean difference and a standard deviation of 0.01% and 0.3%, respectively, from each planned spot weight. These small deviations lead to an excellent agreement in dose comparisons with an average γ passing rate of 99.1%. When each calculation for both planned and zero gantry angles was compared to the measurement, a high correlation in γ values was also observed, also indicating the dosimetric differences are small when a field is delivered at different gantry angles. Utilizing the online beam delivery records, the gantry angle dependencies of the PBS beam delivery were assessed and quantified. The study confirms the variations of the physical properties to be sufficiently small within the clinical tolerances without taking into account the gantry angle variation.